CERVICALGIA: RHEUMATOLOGICAL ASPECTS - N A Shostak; N G Pravdyuk; D N Magomedova (Современная ревматология, 2009)
The paper presents the rheumatological aspects of the neck pain syndrome and the current view of the management and treatment of patients with cervicalgias.